Ekstraksi Karagenan Eucheuma cottonii dari Perairan Nusa Dua Bali dan Pemanfaatannya sebagai Edible Film=Extraction of Carrageenan Eucheuma cottonii from Water Territorial Nusa Two Bali and Benefit as Edible film - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The objectives of this research were to know the influence of carrageenan concentration and palmitate acid to ward physical nature, nature of mechanical and nature of resistance of edible of film carrageenan to water vapour absorbtion, and also to knowthe influence of using of edible film carrageenan to heavy degradation of fruit lengkeng during^iepository. This research was divided into four steps. First steps wasihe extraction of carrageenan by isopropil alcohol and potassium chloride, and characterization of carrageenan yielded. Second steps was characterization edible film of variation concentration carrageenan (0,5%